Responses of soil heterotrophic respiration and microbial biomass to organic and conventional production systems - Dhakal, Kripa; Parajuli, Madhav; Jian, Siyang; Li, Jianwei; Nandwani, Dilip (Frontiers in Soil Science, 2022)
The effects of organic and conventional production systems on crop productivity have been greatly explored, but their effects on soil microbial processes were often neglected. A comparative field study of organic and conventional production systems was conducted at the Tennessee State University research farm to determine soil heterotrophic respiration and microbial biomass carbon. Leafy green vegetables were grown in a conventional production system in an open field, and they were grown in an organic production system, using three different row covers (agribon cloth, insect net, and plastic), and in an open field. Soil samples (0-15cm) were collected from the two production systems. Soil heterotrophic respiration rate (RH), microbial biomass carbon (MBC), and biomass-specific heterotrophic respiration rate (the inverse is used as a proxy for microbial carbon use efficiency) were quantified. The results showed that the conventional production system significantly increased RH relative to the organic system. Organic production system, however, significantly enhanced MBC and reduced biomass-specific respiration rate indicating an increase in carbon use efficiency. Although MBC remained unchanged among the row covers, insect net increased RH and biomass-specific heterotrophic respiration rate. Our results suggest that the organic production system not only promoted soil microbial abundance but also limited soil heterotrophic respiration to the atmosphere governed by the elevated carbon use efficiency.